Cardiovascular-kidney-metabolic syndrome definition and its role in the prevention, risk staging, and treatment. An opportunity for the Nephrology - Aleix Cases; Jose Jesus Broseta; Maria Marqués; Secundino Cigarrán; Juan Carlos Julián; Roberto Alcázar; Alberto Ortiz (Nefrología (English Edition), 2024)
The recent conceptualization of the cardiovascular-kidney-metabolic (CKM) syndrome by the American Heart Association (AHA) opens an opportunity for a multidisciplinary and lifelong approach in the risk stratification, early prevention, and treatment of the vicious circle generated by the interaction of cardiovascular, renal and metabolic risk factors and aggravated by the development of cardiovascular diseases (including their full spectrum: heart failure, atrial fibrillation, coronary heart disease, stroke, and peripheral arterial disease), chronic kidney disease or type 2 diabetes mellitus, with the excess or dysfunctional adiposity as the trigger. Three publications offer the rational basis of a conceptual decalogue and action plan and a new cardiovascular risk stratification equation since the age of 30 that includes measures of renal function/damage, among others, to promote effective cardiovascular, renal, and metabolic prevention. In Spain, we must leverage this momentum to adapt these new concepts to our reality with greater and improved collaboration between primary care and the specialties involved in CKM syndrome, including the formation of multidisciplinary units for the optimal management using a patient-centred approach. Resumen: La reciente conceptualización del síndrome cardiovascular-reno-metabólico (CRM) por la American Heart Association (AHA) abre una oportunidad al abordaje multidisciplinar y desde etapas tempranas de la vida en la estratificación del riesgo, la prevención y el tratamiento precoz del círculo vicioso generado por la interacción de factores de riesgo cardiovasculares, renales y metabólicos y agravado por el desarrollo de enfermedades cardiovasculares (incluyendo todo su espectro: insuficiencia cardíaca, fibrilación auricular, enfermedad coronaria, accidente cerebrovascular, y enfermedad arterial periférica), enfermedad renal crónica o diabetes mellitus tipo 2, con la adiposidad excesiva o disfuncional como sustrato del problema. Un trío de publicaciones ofrecen las bases racionales de un decálogo conceptual y de acción, con nuevas herramientas de estratificación de riesgo cardiovascular desde los 30 años de edad y que incluyen medidas de función/daño renal, entre otras, que permitan una eficaz prevención cardiovascular, renal y metabólica. En España debemos aprovechar este impulso para adaptar los nuevos conceptos a nuestra realidad con una mayor y mejor colaboración entre atención primaria y las diversas especialidades implicadas, incluyendo la creación de unidades multidisciplinares para un manejo óptimo y centrado en el paciente.